Adaptive strategies in tourism destinations amid migration and displacement - della Sala, Valerio (Anais Brasileiros de Estudos Turísticos, 2024)
This study analyses the interplay between migration, displacement and the tourism industry, shedding light on how destinations worldwide adapt to the dynamic challenges posed by these phenomena. As global migration patterns shift and displacement becomes more frequent due to various factors, including conflict, climate change and socio-economic disparities, tourism destinations are at a critical juncture. Quantitative data collection involved surveys distributed to tourists and local businesses in various destinations monitored by the WTO. The study is based on a secondary dataset collected from different tourism destinations globally, representing different geographical locations, cultural contexts and stages of economic development. The dataset includes data obtained from existing literature, reports and official statistics on migration, displacement and tourism. Adaptation strategies used by destinations include community engagement initiatives, sustainable tourism development and the formulation of inclusive policies. In conclusion, this research contributes to a comprehensive understanding of how tourism destinations address the complex challenges of migration and displacement. By illustrating the interconnections between demographic changes, community dynamics and economic resilience, the study provides valuable insights for policymakers, destination managers and researchers seeking sustainable and adaptive solutions in the changing landscape of global tourism.